The Neurochemical Effects of Prazosin Treatment on Fear Circuitry in a Rat Traumatic Stress Model - AYDIN OMAY, BANU; CABADAK, HÜLYA; GÖREN, MEHMET ZAFER (KOREAN COLL NEUROPSYCHOPHARMACOLOGY, 2020)
Objective: The timing of administration of pharmacologic agents is crucial in traumatic stress since they can either potentiate the original fear memory or may cause fear extinction depending on the phase of fear conditioning. Brain noradrenergic system has a role in fear conditioning. Data regarding the role of prazosin in traumatic stress are controversial. Methods: In this study, we examined the effects of prazosin and the noradrenergic system in fear conditioning in a predator stress rat model. We evaluated the direct or indirect effects of stress and prazosin on noradrenaline (NA), gamma-aminobuytyric acid (GABA), glutamate, glycine levels and choline esterase activity in the amygdaloid complex, the dorsal hippocampus, the prefrontal cortex and the rostral pons. Results: Our results demonstrated that prazosin might alleviate defensive behaviors and traumatic stress symptoms when given during the traumatic cue presentation in the stressed rats. However prazosin administration resulted in higher anxiety levels in non stressed rats when the neutral cue was presented. Conclusion: Prazosin should be used in PTSD with caution because prazosin might exacerbate anxiety in non-traumatized subjects. However prazosin might as well alleviate stress responses very effectively. Stress induced changes included increased NA and GABA levels in the amygdaloid complex in our study, attributing noradrenaline a possible inhibitory role on fear acquisition. Acetylcholine also has a role in memory modulation in the brain. We also demonstrated increased choline esterase acitivity. Cholinergic modulation might be another target for indirect prazosin action which needs to be further studied.
Keywords: Noradrenalline; Rostral pons; Cholinergic; Gamma-aminobuytyric acid; Glutamic acid; Glycine; LOCUS-CERULEUS NEURONS; ANIMAL-MODEL; ALPHA-1-ADRENERGIC RECEPTORS; CARDIOVASCULAR-RESPONSES; AMYGDALA; EXTINCTION; ANXIETY; CONSOLIDATION; PROPRANOLOL; ANTAGONISTS